Recent trends on techno-economic assessment (TEA) of sugarcane biorefineries - Mohsen Ali Mandegari; Somayeh Farzad; Johann F. Görgens (Biofuel Research Journal, 2017)
Sustainability challenges, e.g., climate change, resource depletion, and expanding populations, have triggered a swift move towards a circular bio-economy which is expected to evolve progressively in the coming decades. However, the transition from a fossil fuel-based economy to a bio-based economy requires the exploitation of scientific innovations and step changes in the infrastructure of chemical industry. Biorefineries have been extensively investigated for biofuel production from first and second generation feedstocks, whereas some research activities have been conducted on production of biochemical and biopolymers from renewable resources. Techno-economic evaluation of diverse technologies for production of biofuels and biochemical is a crucial step for decision making in the development of bio-economy. This contribution focuses on the economic studies carried out on biorefineries converting sugarcane bagasse, due to its availability and importance in the South African context, into value-added products. Recent studies on biofuel production via biochemical pathway, e.g., ethanol, butanol, or thermochemical pathway, e.g., methanol and bio jet fuel as well as production of biochemicals with high market demands and diverse applications such as lactic acid, succinic acid, and xylitol have been briefly reviewed. In addition, an overview on the production of biopolymers such as polyl-lactic acid and bio-based monomers, i.e., butanediol, from sugarcane bagasse is reported.